Socio-Legal Strategies against a Total Abortion Ban in El Salvador: Alliances in Hostile Contexts - María Angélica Peñas Defago; Violeta Cánaves (Revista Direito GV)
Abstract The case of El Salvador provides unique evidence of how solidarity is possible among different social movements in struggles over abortion law reform and its impact, even in contexts of extreme criminalization. The paper depicts a concrete example of how networks centered on abortion struggles can go beyond feminist movements and national borders, and shows the domestic impact of broadening the scope of the audience, the actors involved, and the spheres where abortion law discussions take place. The article focuses on the evolution of socio-legal mobilization regarding abortion in El Salvador over the last two decades. This evolution is presented through three moments: the first centers on the legal actions that feminist movements orchestrated in the mid-2000's around the Beatriz case. The second moment focuses on the most outstanding features of the “Las 17” campaign – a collaborative and international experience that entailed the submission of seventeen pardon petitions on behalf of women who had been convicted of homicide after having miscarriages. Finally, a third moment entails the socio-legal strategies embraced by feminist movements since 2018 within the framework of the campaign named “Las 17+”.